2016
DOI: 10.1016/j.abrep.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and problematic Internet use among adolescents in Japan: A nationwide representative survey

Abstract: IntroductionJapan is assumed to have serious health and social problems due to Internet overuse, but little is known about the actual conditions. This study was conducted to investigate the prevalence of problematic Internet use (PIU) and associated Internet use in adolescents in Japan.MethodsA nationwide survey of adolescent Internet use was conducted in 2012 and 2013. The participants were 100,050 students from randomly selected junior and senior high schools nationwide who gave valid responses to a self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
64
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 43 publications
(77 reference statements)
16
64
2
8
Order By: Relevance
“…One interesting finding from our data is that the prevalence of PIU was trend‐level higher in young women than in young men, whereas most of the reported female prevalence in other countries is smaller. This result was similar to the result of Mihara et al . and Morioka et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One interesting finding from our data is that the prevalence of PIU was trend‐level higher in young women than in young men, whereas most of the reported female prevalence in other countries is smaller. This result was similar to the result of Mihara et al . and Morioka et al .…”
Section: Discussionsupporting
confidence: 93%
“…One interesting finding from our data is that the prevalence of PIU was trend-level higher in young women than in young men, whereas most of the reported female prevalence in other countries is smaller. This result was similar to the result of Mihara et al 48 and Morioka et al 14 for junior high and high school students in Japan. Tateno et al showed that more men use the Internet for games, whereas more women use the internet for SNS, such as Facebook, Twitter, and LINE.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of students with PIU was slightly higher among female students, though the difference was not significant (Tables , and S1), which is consistent with some previous studies in Japan . It is possible that differences in students’ Internet activities may be related to sex, which would lead to sex differences in the prevalence of PIU, though no conclusions have been reported .…”
Section: Discussionsupporting
confidence: 85%
“…A large‐scale survey on the prevalence of PIU among junior high‐school students in Japan was conducted for the first time in 2012 by the Health Laboratory Research Group using Young's diagnostic criteria . The survey's results showed a 6% prevalence of PIU among junior high‐school students nationwide, which was estimated to be 510 000 adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation